FUNCTIONAL CLUSTERS OF PROTASEMATIC AND SIMPROTASEMATIC LEVELS - HAKOBYAN, ANOUSH (Bulletin of Yerevan University H: Russian Philology, 2019)
The hierarchical system of linguistic objects of different stages has been investigated and for the first time the functional conjunctive, disjunctive and implicative levels and their constituent units were revealed. A five-level classification is proposed. Functional conjunctive, disjunctive and implicative clusters have been revealed, and for each of them protasematic and simprotasematic levels are defined with relevant nuclear and co-nuclear units. We have identified both intra- and inter-level links between the functional units, as well as the issues of qualitative and quantitative intersection of the obtained clusters and their units.
Keywords: cluster, function, conjunction, disjunction, implication, protasematic level, simprotasematic level